Islamic Law Review on Feminism in Household Life - Widodo, Tri; Fadilah, Aidil Risqi (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2024)
This article discusses Islamic Law's review of feminism in domestic life. Feminism, which originally emerged to fight the oppression of women, is now often considered to have deviated from its main objectives, especially in the context of gender roles and traditional values in the household. This research aims to find out the existence of feminism in Indonesia, the review of Islamic Law on feminism in the household, and efforts that can be made to overcome it. Using a descriptive qualitative approach and literature review, this research collected data from various literatures, books and journals. The results show that feminism in Indonesia, which began with figures such as Raden Ajeng Kartini, aims to achieve gender equality and fight patriarchy, but often contradicts the principle of equality in the interpretation of Islamic Law. Islamic law regulates the roles of husbands and wives by emphasising the protection of family rights, although certain interpretations emphasise the wife's obedience to the husband, which can conflict with the principles of feminism. To overcome the impact of feminism in the household, it is important to increase understanding of rights and obligations in Islam, as well as educate the community through seminars and workshops to achieve sakinah, mawadah, and warahmah families.